2011
DOI: 10.1016/j.vaccine.2011.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Probing the attenuation and protective efficacy of a candidate chikungunya virus vaccine in mice with compromised interferon (IFN) signaling

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus that causes explosive outbreaks of febrile illness associated with rash, and painful arthralgia. The CHIK vaccine strain 181/clone25 (181/25) developed by the United States Army Medical Research Institute of Infectious Diseases (USAMRIID) was shown to be well-tolerated and highly immunogenic in phase I and II clinical trials although it induced transient arthralgia in some healthy adult volunteers. In an attempt to better understand the host factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 36 publications
11
64
0
2
Order By: Relevance
“…In addition, natural antibodies present in the sera of uninfected C57BL/6 mice were able to partially inhibit CHIKV (75). Furthermore, therapies based on passively transferred anti-CHIKV neutralizing antibodies conferred protection to A129 mice (42,44,45,70,71,73,(76)(77)(78) and nonhuman primates (37) against CHIKV and protection to mice against more distantly related arthrogenic alphaviruses (43,93,96), establishing the key role of humoral immunity in the control of CHIKV replication. Interestingly, complete protection from CHIKV challenge can be obtained using adoptive transfer of antibodies induced by immunization with a CHIKV/IRES vaccine candidate and occurs in the absence of CD4 ϩ /CD8 ϩ T cells (42); a titer of 35 for neutralizing antibodies was sufficient to protect mice from a challenge with 100 PFU of CHIKV (42).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, natural antibodies present in the sera of uninfected C57BL/6 mice were able to partially inhibit CHIKV (75). Furthermore, therapies based on passively transferred anti-CHIKV neutralizing antibodies conferred protection to A129 mice (42,44,45,70,71,73,(76)(77)(78) and nonhuman primates (37) against CHIKV and protection to mice against more distantly related arthrogenic alphaviruses (43,93,96), establishing the key role of humoral immunity in the control of CHIKV replication. Interestingly, complete protection from CHIKV challenge can be obtained using adoptive transfer of antibodies induced by immunization with a CHIKV/IRES vaccine candidate and occurs in the absence of CD4 ϩ /CD8 ϩ T cells (42); a titer of 35 for neutralizing antibodies was sufficient to protect mice from a challenge with 100 PFU of CHIKV (42).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, IFN-␣/␤ knockout mice (A129 mice) exhibited severe CHIKV disease (62-64, 66, 92), confirming the key role of type I IFNs in the control of CHIKV infection, by restricting virus replication early in the infection, although their effects are not enough to eliminate CHIKV from infected hosts. In fact, it has been reported that in the absence of an IFN-␣/␤ response, IFN-␥ partially controls CHIKV replication (77). Therefore, our results showing that MVA-CHIKV promotes a strong innate immune response in human macrophages and moDCs, upregulating the expression of IFN-␤, IFN-inducible genes (IFIT1 and IFIT2), and some key cytosolic sensors that lead to antiviral IFN production (RIG-I and MDA-5), could be relevant to promoting the recruitment of leukocytes to sites of infection and therefore be an efficient antiviral defense in the control of CHIKV infection after challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sections for hematoxylin and eosin (H&E) staining were prepared as previously described. 19,20 Statistics. Differences in animal weights were analyzed using two-way analysis of variance with a Tukey-Kramer posthoc test.…”
Section: Methodsmentioning
confidence: 99%